Short-term immune-checkpoint inhibition partially rescues perturbed bone marrow hematopoiesis in mismatch-repair deficient tumors - Paula Krone; Annabell Wolff; Julia Teichmann; Johanna Maennicke; Julia Henne; Leonie Engster; Inken Salewski; Wendy Bergmann; Christian Junghanss; Claudia Maletzki (OncoImmunology)
Wide-spread cancer-related immunosuppression often curtails immune-mediated antitumoral responses. Immune-checkpoint inhibitors (ICIs) have become a state-of-the-art treatment modality for mismatch repair-deficient (dMMR) tumors. Still, the impact of ICI-treatment on bone marrow perturbations is largely unknown. Using anti-PD1 and anti-LAG-3 ICI treatments, we here investigated the effect of bone marrow hematopoiesis in tumor-bearing Msh2loxP/loxP;TgTg(Vil1-cre) mice. The OS under anti-PD1 antibody treatment was 7.0 weeks (vs. 3.3 weeks and 5.0 weeks, control and isotype, respectively). In the anti-LAG-3 antibody group, OS was 13.3 weeks and thus even longer than in the anti-PD1 group (p = 0.13). Both ICIs induced a stable disease and reduced circulating and splenic regulatory T cells. In the bone marrow, a perturbed hematopoiesis was identified in tumor-bearing control mice, which was partially rescued by ICI treatment. In particular, B cell precursors and innate lymphoid progenitors were significantly increased upon anti-LAG-3 therapy to levels seen in tumor-free control mice. Additional normalizing effects of ICI treatment were observed for lin−c-Kit+IRF8+ hematopoietic stem cells, which function as a “master” negative regulator of the formation of polymorphonuclear-myeloid-derived suppressor cell generation. Accompanying immunofluorescence on the TME revealed significantly reduced numbers of CD206+F4/80+ and CD163+ tumor-associated M2 macrophages and CD11b+Gr1+ myeloid-derived suppressor cells especially upon anti-LAG-3 treatment. This study confirms the perturbed hematopoiesis in solid cancer. Anti-LAG-3 treatment partially restores normal hematopoiesis. The interference of anti-LAG-3 with suppressor cell populations in otherwise inaccessible niches renders this ICI very promising for subsequent clinical application.